2001
DOI: 10.1097/00001756-200103260-00019
|View full text |Cite
|
Sign up to set email alerts
|

Emotional expression boosts early visual processing of the face: ERP recording and its decomposition by independent component analysis

Abstract: To investigate the hypothesis that early visual processing of stimuli might be boosted by signals of emotionality, we analyzed event related potentials (ERPs) of twelve right-handed normal subjects. Gray-scale still images of faces with emotional (fearful and happy) or neutral expressions were presented randomly while the subjects performed gender discrimination of the faces. The results demonstrated that the faces with emotion (both fear and happiness) elicited a larger negative peak at about 270 ms (N270) ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
114
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 22 publications
30
114
5
Order By: Relevance
“…The EPN is enhanced for emotional relative to neutral stimuli, for both verbal and non-verbal material including faces (Schacht & Sommer, 2009;Schupp Markus, Weike, & Hamm, 2003;Schupp et al, 2004;Rellecke et al, 2013). Like the N170, the EPN is commonly reported to be most pronounced for threatrelated expressions (i.e., fearful and angry) compared to neutral and happy expressions (e.g., Schupp et al, 2004;Rellecke, Palazova, Sommer, & Schacht, 2011), although there are reports of a general emotion effect with more negative amplitudes for both threatening and happy expressions compared to neutral expressions (Sato et al, 2001;Schupp, Flaisch, Stockburger, & Junghöfer, 2006). Therefore this effect has been suggested to reflect enhanced processing of emotionally salient faces in general or of threatening faces in particular (i.e., fearful and angry) in temporo-occipital areas possibly including occipital gyrus, fusiform gyrus and Superior Temporal Sulcus regions (Schupp et al, 2004).…”
Section: Early Event-related Potentials In Facial Expression Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…The EPN is enhanced for emotional relative to neutral stimuli, for both verbal and non-verbal material including faces (Schacht & Sommer, 2009;Schupp Markus, Weike, & Hamm, 2003;Schupp et al, 2004;Rellecke et al, 2013). Like the N170, the EPN is commonly reported to be most pronounced for threatrelated expressions (i.e., fearful and angry) compared to neutral and happy expressions (e.g., Schupp et al, 2004;Rellecke, Palazova, Sommer, & Schacht, 2011), although there are reports of a general emotion effect with more negative amplitudes for both threatening and happy expressions compared to neutral expressions (Sato et al, 2001;Schupp, Flaisch, Stockburger, & Junghöfer, 2006). Therefore this effect has been suggested to reflect enhanced processing of emotionally salient faces in general or of threatening faces in particular (i.e., fearful and angry) in temporo-occipital areas possibly including occipital gyrus, fusiform gyrus and Superior Temporal Sulcus regions (Schupp et al, 2004).…”
Section: Early Event-related Potentials In Facial Expression Researchmentioning
confidence: 96%
“…A growing number of studies have now reported enhanced P1 amplitude for fearful relative to neutral faces (e.g., Batty & Taylor, 2003;Pourtois, Grandjean, Sander, & Vuilleumier, 2004;Sato, Kochiyama, Yoshikawa & Matsumura, 2001;Smith, Weinberg, Moran, & Jajcak, 2013;Wijers & Banis, 2012). It has been suggested that early occipito-temporal visual areas could be activated to a larger extent by intrinsically salient, threat-related stimuli, via possible projections from a subcortical route involving the amygdala (Vuilleumier & Pourtois, 2007).…”
Section: Early Event-related Potentials In Facial Expression Researchmentioning
confidence: 99%
“…Following the N1, the early posterior negativity (EPN), a relative negativity for emotional compared to neutral stimuli occurs between 200-300 ms at occipito-temporal sites. The EPN is increased for anxious or angry facial expressions compared to happy or neutral ones (Sato et al 2001;Schupp et al 2004b). Furthermore, during emotional face processing a late positive potential (LPP) appears over centro-parietal regions.…”
Section: Emotional Face Perceptionmentioning
confidence: 99%
“…In particular, negative facial expressions have been found to modulate the amplitude (sometimes the latency, see Williams et al [2004]) of various evoked potential components over a large temporal window following face onset, from early perceptual responses [Ashley et al, 2004, Batty andTaylor, 2003;Halgren et al, 2000;Pizzagalli et al, 1999Pizzagalli et al, , 2002 through the face-selective N170 [Campanella et al, 2002] or other early occipito-temporal negativity [Sato et al, 2001;Schupp et al, 2004], to the amodal P3 wave [Carretie and Iglesias, 1995;Meinhardt and Pekrun, 2003;Liddell et al, 2004] and other late sustained modulations [Krolak-Salmon et al, 2001]. …”
Section: Introductionmentioning
confidence: 99%